2017
DOI: 10.6063/motricidade.7573
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anthropometric characteristics and physical abilities in a soccer season: comparison between U-15, U-17 and U-19

Abstract: ARTIGO ORIGINAL | ORIGINAL ARTICLE RESUMOO objetivo do presente estudo foi analisar a evolução das características antropométricas e capacidades físicas, ao longo de uma época desportiva, em jovens jogadores de futebol. Um total de 50 jogadores sub-15 (n= 16, 14.0±0.1 anos), sub-17 (n= 14, 15.6±0.5 anos) e sub-19 (n= 20, 17.2±0.7 anos) foram controlados em 3 momentos de avaliação: após o período de preparação geral (pré-época), após a 1ª fase competitiva (meio-época) e após a 2ª fase competitiva (pós-época). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Flexibility in amputee football is crucial for sporting success in situations such as stealing, dribbling, controlling the ball coming off the ground at high and sprint acceleration. In the literature, Silva and Morouço (2017) found no significant differences in the flexibility parameter of football players under 15 years of age in their study. In the investigation, Nikolaidis et al (2014) found no significant differences in the flexibility parameter playing the position of football players.…”
Section: Discussionmentioning
confidence: 53%
“…Flexibility in amputee football is crucial for sporting success in situations such as stealing, dribbling, controlling the ball coming off the ground at high and sprint acceleration. In the literature, Silva and Morouço (2017) found no significant differences in the flexibility parameter of football players under 15 years of age in their study. In the investigation, Nikolaidis et al (2014) found no significant differences in the flexibility parameter playing the position of football players.…”
Section: Discussionmentioning
confidence: 53%